OC-034 Salvage of central venous catheters in HPN catheter-related blood stream infections is safe and effective: 18 years experience from a national centre. (28th May 2012) - Dibb, M; Carlson, G; Abraham, A; Shaffer, J; Teubner, A; Lal, S
Abstract : Introduction: Catheter-related blood stream infections (CRBSI) are a serious and life-threatening complication in the provision of HPN. European guidelines recommend antibiotic salvage of central venous catheters (CVCs) with CRBSI, wherever possible, to minimise repeated catheter replacement and preserve venous access, but this is based on limited reported evidence. 1 Methods: Data were analysed from a prospectively-maintained register of all confirmed CRBSIs occurring in patients on HPN since January 1993 to December 2011, managed in a National Intestinal Failure Unit (IFU). Diagnosis of a CRBSI was based on quantitative and qualitative assessment of central and peripheral blood cultures and pour plates. Treatment was commenced according a standardised protocol involving antibiotic and urokinase CVC locks and systemic antibiotic administration. Results: A total of 299 CRBSIs occurred in 138 patients (66 single CRBSI, 72 multiple CRBSI) with 377 patients having no catheter infections. The mean number of catheter days prior to developing an infection was 712 (range 5–6128). This represents an overall rate of infection in all patients of 0.39 per 1000 catheter days. A single microorganism caused 87.9% of infections, most commonly coagulase negative staphylococcus (CNS; 49.5% cases). Overall catheter salvage was achieved in 62.2% (intention to treat) of all patients presenting with CRBSIs (Coagulase negative staphylococcus 70.5% (105/149), MRSA 36.4% (4/11), polymicrobial infections 58.3% (21/36), other Staphylococcus aureus 48.3% (14/29) and miscellaneous 56.8% (42/74)). Line salvage was not attempted in 46 patients because of life-threatening sepsis (n=18), fungal line infection (n=7), mechanical catheter problems (eg, co-existing line fracture; n=18) and tunnel line infection (n=3). The catheter was removed in 37.7% (95/299) of cases. There were five deaths in patients admitted to the IFU for management of the CRBSI. Conclusion: This is the largest reported series of catheter salvage in CRBSIs and demonstrates that catheter salvage according to a standardised protocol is a safe and effective strategy to preserve essential venous access in patients dependent on HPN. Competing interests: None declared. Reference: 1. Pittiruti M, Hamilton H, Biffi R, et al. ESPEN guidelines on parenteral nutrition: central venous catheters (access, care, diagnosis, and therapy of complications). Clin Nutr 2009;28 :365–77.